Robust adaptive fault tolerant control for a process with actuator faults. (August 2020) - Arıcı, Mehmet; Kara, Tolgay
Abstract: This paper studies design and implementation of an enhanced multivariable adaptive control scheme for an uncertain nonlinear process exposed to actuator faults. For adaptive fault compensation, a model reference adaptive control (MRAC) strategy is utilized as main controller. A new adaptation algorithm making possible to improve transient performance of adaptive control is integrated to the controller. With the help of further modifications, some restrictive conditions on multivariable adaptive design are relaxed so that the system requires less plant information. The resulting controller has a simpler structure than the other matrix factorization based controllers. At the final stage of design, a robust adaptive control scheme is obtained with consideration of practical implementation problems such as sensor noises, external disturbances and unmodeled​ system dynamics. It is proved that the controller guarantees closed-loop signal boundedness and asymptotic output tracking. Real-time experiment results acquired from quadruple tank benchmark system are presented in order to exhibit the effectiveness of the proposed scheme. Highlights: An improved multivariable robust adaptive control scheme is obtained with consideration of practical implementation problems such as sensor noises, external disturbances and unmodeled​ system dynamics along with actuator faults. A new adaptation law that is based on a method firstly used for optimization purposes is integrated to the controller so as to give the opportunity to increase the learning rate of adaptation algorithm without causing high frequency oscillation in control signal. A multiplier is integrated to the controller such that it gives us the opportunity to change learning rate freely and allows to obtain a simpler controller structure than the other matrix factorization based controllers. Closed-loop stability and asymptotic output tracking for the resulting controller are shown to be preserved in the presence of modeling uncertainty, sensor noise, structural changes and disturbance stem from actuator faults. Since the new controller is previously tested via computer simulations only, a real quadruple tank process setup with various actuator fault scenarios is used as a case study in order to show effectiveness of the control scheme.